Pengaruh Variasi Pencampuran Tepung Talas Bogor (Colocasia esculenta L. Schott) Dan Kacang Merah (Phaseolus Vulganis L.) Terhadap Sifat Fisik, Tingkat Kesukaan, Kadar Protein Dan Kadar Serat Pada Cookies Talas Rendah Protein - Bella Indri Kaltari; Setyowati Setyowati; Devillya Puspita Dewi (Poltekkes Kemenkes Yogyakarta, 2016)
Background: Bogor taro is one of potential carbohydrate source which is high calcium and phosphor but low fat. Kidney beans is one kind of nuts that can be processed into various products. Kidney bean have low glycemic index with 4 grams of fiber each 100 grams of it has. Objective: To identify the effect of variations of Bogor taro flour (Colocasia esculenta L. Schott) and kidney beans (Phaseolus vulganis L.) mixing variation on physical characteristic, hedonic scalling, protein and fiber level of taro cookies. Methods: This research was a true experimental study which used simple randomized design with 3 units and 4 variations of cookies (100%:0%, 90%:10%, 80%:20%, 70%:30%) of taro flour and kidney bean without any repetition. Assesment of physical characteristic used Hedonic Scale Test Form. The results of physical characteristic were analyzed using Kruskal-Wallis analysis and continued by Mann-Whitney analysis. Protein and fiber level were analyzed using ANOVA analysis and continued by Post Hoc Test (Tukey). Results: There was no effect of Bogor taro flour and kidney beans mixing variation to colour, taste, and flavor, but there was an effect to the texture. There was an effect Bogor taro flour and kidney beans mixing variation on protein and fiber level. Formula 70%: 30% was the best taro cookies variations. Conclusion: There was an effect of Bogor taro flour with kidney beans mixing variation to physical characteristic, hedonic scalling (texture) (p=0,011), protein and fiber level (p=0,000). Keywords: Cookies, Bogor Taro Flour, Kidney Beans, Protein, Fiber